1995
DOI: 10.2166/wst.1995.0145
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of organic solids in gravel-bed constructed wetlands

Abstract: The effects of wastewater loading rate and planting with Schoenoplectus validus (soft-stem bulrush) on the accumulation of organic matter were investigated in four pairs of gravel-bed constructed wetlands. The planted and unplanted wetland pairs, each supplied with a different hydraulic loading of dairy farm wastewaters pre-treated in an anaerobic and aerobic lagoon, had received cumulative suspended solids loadings (∼ 82% volatile) of between ∼ 1.6 and 5.4 kg m−2 over a 22 month period. Vertical and horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
4
10

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 0 publications
5
65
4
10
Order By: Relevance
“…In agreement with findings reported by Tanner et al [39] and Tang et al [40], the OM accumulation was highest in the inlet zone of the Sadowa wetland, but in some cases the OM content also increased in the outlet zone of the HSFCW (Figure 3). Contrary to our results, Tanner and Sukias [41] observed higher OM accumulation in the top layer (<10 cm) of planted and unplanted constructed wetlands. Drizo et al [42] found a significant inverse relationship between P concentration in wastewater flowing through a bed planted with macrophytes and distance from the inlet.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with findings reported by Tanner et al [39] and Tang et al [40], the OM accumulation was highest in the inlet zone of the Sadowa wetland, but in some cases the OM content also increased in the outlet zone of the HSFCW (Figure 3). Contrary to our results, Tanner and Sukias [41] observed higher OM accumulation in the top layer (<10 cm) of planted and unplanted constructed wetlands. Drizo et al [42] found a significant inverse relationship between P concentration in wastewater flowing through a bed planted with macrophytes and distance from the inlet.…”
Section: Discussioncontrasting
confidence: 99%
“…Fan et al found that plants did not play an important role in the removal of organic carbon [24]. However, Tanner and Sukias compared accumulation rates of organic matter in planted versus unplanted treatment beds, and found that the accumulation rates were higher in the planted systems [7].…”
Section: Removal Efficiency Of Cod In Vertical Flow Constructed Wetlandsmentioning
confidence: 99%
“…There are some disputes on the function of wetland plants. Many studies have reported the importance of the presence of vegetation in subsurface flow-constructed wetlands, which might affect the development of clogging [7,8]. However, some studies have suggested that plants could benefit the Sub-surface Flow Constructed Wetlands (SSFCWs) by making the substrate more porous to increase the hydraulic conductivity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The highest thicknesses were observed in CWs cultivated with alligator weed. Some authors have shown the presence of this layer with thicknesses ranging from 10 to 30 cm (TANNER & SUKIAS, 1995;ALCABAR, 2010;KNOWLES et al, 2011). Much has been studied regarding the functions and benefits of plants in wastewater treatment: removal of nutrients, oxygen transfer to the substrate, support for the growth of biofilm of bacteria (rhizomes and roots), as well as improvement in substrate permeability (KADLEC & WALLACE, 2008).…”
Section: Resultsmentioning
confidence: 99%